ANALISIS PENGARUH KUALITAS TEKNIS, KUALITAS FUNGSIONAL DAN CITRA INSTANSI TERHADAP KEPUASAN SATUAN KERJA PENGGUNA JASA SEKSI PENGELOLAAN KEKAYAAN NEGARA (KPKNL) JAMBI - Istiqomah Handayani (Jurnal Dinamika Manajemen, 2013)
Quality of service is the requirement of service user especially for public perception on the government services where the service quality is still low. The purpose of this study was to determine the effect of the quality of government services by using the theory of Gronroos that is technical quality, functional quality and corporate image to the satisfaction of service users. This research uses explanatory survey, data were collected through questionnaires, interviews and observation. Based on the results : simultaneously technical quality functional quality and corporate image has a significant influence on satisfaction. And partially, only the corporate image that have a significant effect on service user satisfaction KPKNL Jambi Keywords : Technical quality, functional quality, corporate image and service user satisfaction